2020
DOI: 10.1136/heartjnl-2020-317059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma big endothelin-1 in left ventricular non-compaction cardiomyopathy

Abstract: ObjectiveTo determine the prognostic role of big endothelin-1 (ET-1) in left ventricular non-compaction cardiomyopathy (LVNC).MethodsWe prospectively enrolled patients whose LVNC was diagnosed by cardiac MRI and who had big ET-1 data available. Primary end point was a composite of all-cause mortality, heart transplantation, sustained ventricular tachycardia/fibrillation and implanted cardioverter defibrillator discharge. Secondary end point was cardiac death or heart transplantation.ResultsAltogether, 203 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has predictive value in patients with chronic heart failure ( 25 ), and its predictive value is not inferior to those of hemodynamic monitoring indicators ( 26 ). In patients with arrhythmia and cardiomyopathy, high big ET-1 level has a certain predictive value for death, malignant arrhythmia, heart transplantation, and other adverse events ( 27 – 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has predictive value in patients with chronic heart failure ( 25 ), and its predictive value is not inferior to those of hemodynamic monitoring indicators ( 26 ). In patients with arrhythmia and cardiomyopathy, high big ET-1 level has a certain predictive value for death, malignant arrhythmia, heart transplantation, and other adverse events ( 27 – 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Except for the potential etiological role of big ET-1 in CAE, this biomarker has been found to be a poor prognosis factor in many cardiovascular diseases including atrial fibrillation, acute myocardial infarction, and left ventricular non-compaction cardiomyopathy (8)(9)(10). Moreover, ET-1 is a key player in endothelial dysfunction and is associated with systemic inflammation (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has the same biological importance as ET-1, a higher concentration, and longer half-life in the peripheral blood (7). Previous studies have identified high levels of big ET-1 as a risk factor for poor prognosis in cardiovascular diseases including atrial fibrillation, acute myocardial infarction, and left ventricular non-compaction cardiomyopathy (8)(9)(10). It has also been reported as a biomarker for predicting the presence of coronary artery ectasia (11).…”
Section: Introductionmentioning
confidence: 99%
“…All the Virchow's triad factors-sluggish blood flow in deep intertrabecular recesses, local myocardial injury, and hypercoagulability/stasis of flow-which contribute to formation of LV thrombus, are present in NCCM, which can also be associated with a hypercoagulability state due to overexpression of factor VIII and endothelin-1. 50 In the current literature, two large studies have highlighted a direct association between NCCM and juvenile 'cryptogenic' stroke: 12-14% patients with NCCM and no other concomitant comorbidities or risk factors (i.e. PFO) experienced an undetermined thromboembolic event, confirming that NCCM may carry a cardioembolic risk per se.…”
Section: Noncompaction Cardiomyopathy Per Sementioning
confidence: 92%
“…All the Virchow's triad factors—sluggish blood flow in deep intertrabecular recesses, local myocardial injury, and hypercoagulability/stasis of flow—which contribute to formation of LV thrombus, are present in NCCM, which can also be associated with a hypercoagulability state due to overexpression of factor VIII and endothelin‐1. 50 …”
Section: Thromboembolic Risk In Noncompaction Cardiomyopathymentioning
confidence: 99%